Chemical characterization by ultrahigh-resolution mass spectrometry analysis of acid-extractable organics from produced water extracted by solvent-terminated dispersive liquid-liquid microextraction - de Aguiar, Deborah V.A.; da Silva, Thais A.M.; de Brito, Talita P.; dos Santos, Gabriel F.; de Carvalho, Rogério M.; Medeiros Júnior, Iris; Simas, Rosineide C.; Vaz, Boniek G. (Fuel (Guildford), 2021)
[Display omitted] •A greener methodology for extraction of naphthenic acids from produced water using solvent-terminated dispersive liquid-liquid microextraction (ST-DLLME) is proposed.•Different solvent systems and pH samples are used for increase the NAs extraction efficiency.•Ultra-high resolution mass spectrometry analysis is performed to characterize the extracts of naphthenic acids.•Solvent system nonpolar such as ST 2 at pH 7 and 10 demonstrated the highest extraction efficiency. Produced water by the offshore oil industry represents a significant environmental problem due to the high volume generated and its toxicity. Therefore, new methods are necessary to characterize the produced water and, consequently, to provide an appropriate destination. Here, we used solvent-terminated dispersive liquid-liquid microextraction (ST-DLLME) followed by ultrahigh-resolution mass spectrometry (UHRMS) analysis to extract and characterize naphthenic acids (NAs) from produced water (PW). ST-DLLME is based on a ternary mixture of solvents classified as dispersive, extractor, and demulsifying solvents to ensure analyte extraction efficiency. After that, seven solvent systems at three pH values (2, 7, and 10) were used to study the influences of the sample pH and organic-phase polarity. The relationship between pKa and pH affects the equilibrium between ions and molecules in the aqueous phase, impacting the extraction efficiency. The results showed that at pH 2, the extractability of NAs is directly affected by the dielectric constant of the dispersive solvent. Therefore, when dichloromethane was employed as a dispersive solvent, ST-DLLME presented a better performance, and NA species within an extensive DBE range (1 – 8) and range of carbon numbers (C7 – C18) were extracted. At pH 7 and 10, the solvent system that employed cyclohexane as a nonpolar dispersive solvent demonstrated the highest extraction efficiency, whereas nonpolar NA species with a carbon number greater than C22 could be extracted. Moreover, solutions at pH 7 and 10 expressed more comprehensive molecular formulas for the corresponding compounds than those at pH 2. In summary, ST-DLLME has become a valuable analytical tool for extracting NAs from PW since this extraction technique minimizes the consumption of samples and solvents.